Banking regulation and banking crises Probability in european countries - M. M. Mursalov (Финансы: теория и практика, 2022)
The main hypothesis of the paper was the thesis that banking regulation is intended to minimize the probability of financial instability, including banking crises, which have long-lasting and destructive consequences for the economy.The practical aim of this investigation is to explore the impact of banking regulation instruments on the banking crisis probability. Despite a large and growing body of literature that has investigated the role of banking regulation in ensuring financial stability, only a few of them explored the aspect of this problem we are considering, and this constitutes the scientific novelty of the research.The results confirm the effectiveness of banking regulation in predicting periods of stability in banking systems.Based on the use of bibliometric analysis with the software tool VOSviewer v.1.6.10, the main patterns in the theory of banking regulation development have been identified. To conduct an empirical analysis, the author used a database of eleven European countries from 1998 to 2017, whose banking systems had manifestations of a systemic banking crisis. Binary modeling (logit model) was used as a scientific and methodological tool for statistical research. The conducted empirical analysis declared the need to tighten banking regulations in the field of non-performing loan control since it leads to an increase in the banking crisis probability. The results of binary modeling also emphasized the importance of macroeconomic and monetary factors, the neglect of which leads to the vulnerability of banking institutions and, consequently, to banking crises.An important conclusion of the analysis is that in order to minimize systemic banking crises, it is necessary to ensure the achievement of the target parameters of the main macroeconomic indicators, expressed in terms of the optimal level of inflation and annual GDP growth. The proposed binary model can be used to further study the causes of a banking crisis, as well as methodological and empirical clarification of the role of banking regulation in the probability of its occurrence.